2016
DOI: 10.1038/nphys3613
|View full text |Cite
|
Sign up to set email alerts
|

Optically controlled dense current structures driven by relativistic plasma aperture-induced diffraction

Abstract: (2016). Optically controlled dense current structures driven by relativistic plasma aperture-induced diffraction. Nature Physics, 12, 505-512. DOI: 10.1038/nphys3613 General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights.Take down policy The Research Porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…Therefore, the analysis is well suited to make meaningful predictions regarding electron acceleration in near-critical and over-critical plasmas, provided that such plasmas are relativistically transparent to the incoming high-intensity laser pulse 28,29 . However, wave propagation becomes a crucial aspect in this case and it should be addressed selfconsistently 30 taking into account transverse laser pulse dimensions and its polarization 31,32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, the analysis is well suited to make meaningful predictions regarding electron acceleration in near-critical and over-critical plasmas, provided that such plasmas are relativistically transparent to the incoming high-intensity laser pulse 28,29 . However, wave propagation becomes a crucial aspect in this case and it should be addressed selfconsistently 30 taking into account transverse laser pulse dimensions and its polarization 31,32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Signature features in the spatial-intensity distribution of the resultant ion beam, including the onset of transverse instabilities and differences in the directionality, show that TNSA, RPA, and transparency-enhanced processes can all occur at different phases of the interaction. [20][21][22] In this article, a characterization of the intra-pulse transition from the radiation pressure-dominated to the relativistic transparency regime in ultrathin foil targets is presented. By measuring changes to the divergence of a low-energy, annular component of the proton beam, the time within the laser pulse envelope at which relativistic induced transparency (RIT) occurs can be inferred.…”
Section: Intra-pulse Transition Between Ion Acceleration Mechanisms Imentioning
confidence: 99%
“…The most salient results for all three polarization cases of the collective electron motion investigation for this target undergoing significant relativistic transparency are shown in Figures 5(a-c). A more detailed analysis of these results are reported in Gonzalez-Izquierdo et al [19] . A double-lobe distribution in the electron density is measured in the case of linearly polarized light, with the axis separating the lobes orientated perpendicular to the laser polarization axis ( Figure 5(a)).…”
Section: The Relativistically Transparency Dominant Regimementioning
confidence: 89%
“…As n c and λ are intrinsic parameters of the laser, the effective parameter which determines the onset of relativistic transparency in ultrathin targets is the areal density, n e l. We have recently reported on the collective response of target electrons to intense laser light in ultrathin targets for which significant hole boring occurs, in the near-critical density regime [16][17][18][19] . Using picosecond duration laser pulses and ultrathin Al targets, Powell et al [17] demonstrated that the onset of transparency can produce a directed jet of energetic electrons in the expanding plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation